Penggunaan Aplikasi Spotify Sebagai Media Baru Layanan Streaming Musik pada Generasi Z - Yolanda, May Nessa; Aini, Husnatul; Sari, Dian Mustika (LITERAKOM: Jurnal Literasi dan Komunikasi, 2024)
This research discusses the use of the Spotify application as new media for music streaming services in generation Z. The focus of this research is the music consumption behavior of social sciences faculty students. This research uses a qualitative approach and uses and gratifications theory as a theoretical basis. Data was obtained through literature study and interviews with related sources. The research results show that the Spotify application provides various features that meet the needs of its users, such as ease of finding new music, creating personal playlists, and podcast features that support self-development. Spotify is not only a platform for listening to music, but also meets the psychological and emotional needs of its users. With the existence of new media such as spotify, it has modernized the consumtion behaviour of studentes who use spotify as a forum for shanneling public speaking talents and even as a medium for channeling feelings.